Talking for Britain : a journey through the nation's dialects. - Elmes, Simon, ....- (London : Penguin, 2005)
Every region of Britain has its own distinct and constantly evolving way of talking, and this magnificent new survey pinpoint precisely what people say where - and how they say it. If you're puzzled by a Yorkshire invitation to laik out, uncertain wether to take an umbrella when told it's going to sile down, or ever wondered where you might encounter a petty, snicket or even a launder, then this fascinating and superbly browsable book will provide the answers.
Keywords: Engels -- Taalgebruik; Engels -- Woordenboeken; Engelse dialecten -- Spraakkunst